(untitled) (Research, Society and Development, 2022)
Objective: To describe the main etiologies responsible for the development of the different presentations of pericarditis. Methodology: This is a narrative literature review based on SciELO, Google Scholar, LILACS, Brazilian Journal of Health Review, Research, Society and Development and Pubmed platforms from January to March 2022, using the following descriptors: pericarditis, cardiac information and pericardiopathies. Thirty-six articles were found in Portuguese, English and Spanish, which were later submitted to the analysis and selection criteria. Twenty articles were selected because they were in full, evidence-based, current, with clear, direct language and evidence-based, discarding the others that were duplicated, arranged in the form of abstracts and that did not meet the proposed objective. Results: Pericarditis is an inflammatory process of the membranous space that surrounds the heart. This involvement can take different forms depending on its period, the etiological agent and the underlying clinical impacts. There is in the literature the classification of pericarditis in acute and chronic forms, the latter to mention the first episodes and also extensive and evolutionary processes and these have infectious agents or not. Infectious agents can be viral, bacterial, fungal and parasitic agents and those that are manifestations of systemic diseases such as autoimmune, neoplasms, metabolic or drug-induced. Conclusion: Pericarditis is a complex pathological event, most of the time it is benign and without fanfare because it is of viral origin and is easily treated, but other agents need diagnosis and advanced therapeutic management to avoid morbidity and mortality.